Diseño de un aerogenerador de eje vertical con guía "paso a paso" para su implementación en una finca de 2000 M2 (2020)
This project is based on the design of a vertical axis wind turbine for the rural area of ​​the municipality of Quetame, Cundinamarca, in which a methodology was carried out in order to fulfill a series of objectives, which begin with the collection information by consulting different bibliographic sources on wind turbines, taking into account the most important aspects of vertical axis wind turbines; Subsequently, the study of the climatic conditions of the area was carried out, the development of the project continued, evaluating the alternatives on the profile of the palette, selecting the most suitable for the design. Next, the detailed design of the turbine was carried out following the "step by step" procedure, in which the corresponding calculations required by the machine for correct operation were carried out, such as the dimensions of the wind turbine, power system, system generation, structural system and control system.